Impact of nitrification inhibitor application on the nematode community in dairy pasture soil - Aalders, L.T.; Bell, N.L. (New Zealand Plant Protection, 2008)
Use of the nitrification inhibitor dicyandiamide (DCD) on New Zealand dairy farms is increasing in an attempt to minimise nitrate losses to ground water from urine patches To study the impact of DCD on soil nematodes samples were collected from a field trial in Waikato where 27 kg/ha was applied on 11 occasions over 12 months and total nematodes and the nematode community analysed Of the nematode families genera and indices calculated only populations of plantfeeding Pratylenchus (lesion) nematodes were significantly different between DCD treated and untreated plots These results suggest that frequent small applications of DCD over a single year had no major effect on the nematode community from bulk soil